Ezetimibe and Improving Cardiovascular Outcomes: Current Evidence and Perspectives - Akshyaya Pradhan; Monika Bhandari; Rishi Sethi (Cardiology Research and Practice)
Low-density lipoprotein lowering with statins has convincingly and consistently proven to reduce cardiovascular events in both primary and secondary prevention. However, despite high-dose statin therapy, residual cardiovascular risk remains and many patients also do not tolerate statins. Ezetimibe was initially projected as a frontline alternative to statin. It is an intestinal cholesterol absorption inhibitor with modest LDL lowering effects. But, major studies failed to demonstrate any beneficial effect of CV outcomes, and the drug was relegated to oblivion. IMPROVE-IT, a contemporary, large, and well-designed trial, unequivocally demonstrated reduction in CV outcomes with ezetimibe when added to statin therapy. The benefits are seen in both sexes, elderly, CKD, diabetes mellitus, and in patients with prior CABG. It also reduces biomarkers and induces plaque regression like statins. The drug has now established itself as an add-on therapy to statin when monotherapy fails to achieve LDL goals and when it is not tolerated. The combination therapy has excellent safety and efficacy record. It has now been endorsed by major guidelines too in management of dyslipidemia. Yes, ezetimibe can indeed improve cardiovascular outcomes!